Peroral endoscopic myotomy (POEM): a comparative study between Chagasic and idiopathic achalasia - Farias, Galileu F.A. (Endosc Int Open, 2020)
Background and study aims  Achalasia can be classified as either primary (idiopathic) achalasia or secondary achalasia, which is a consequence of another systemic disease. Peroral endoscopic myotomy (POEM) is an effective and safe treatment for achalasia. We evaluated the efficacy and safety of POEM in patients with Chagasic achalasia compared to idiopathic achalasia. Patients and methods  We evaluated POEM procedures performed at a single institution from November 2016 to January 2018. Demographic data, Eckardt score, lower esophageal sphincter (LES) pressure, body mass index, post-operative erosive esophagitis, adverse events, length of hospital stay, and procedure-related parameters were analyzed. Results  Fifty-one patients underwent POEM as a treatment for achalasia in this period (20 patients with Chagasic and 31 with Idiopathic etiology). The overall clinical success rate was 92.1 %, with no statistical difference between groups (90 % in the Chagasic group vs. 93.5 % in the Idiopathic group, P  = 0.640). Both groups had significant reduction in Eckardt score and in LES pressure, and increase in bodey mass index (BMI) at 1-year follow-up. There was no statistical difference between groups regarding Eckardt score ( P  = 0.439), LES pressure (p = 0.507), BMI ( P  = 0.254), post erosive esophagitis (35 % vs. 38.7 %, P  = 0.789), adverse events (30 % vs. 12 %, P  = 0.163,) length of hospital stay (3.75 days vs. 3.58 days, P  = 0.622), and operative time (101.3 min vs. 99.1 min, P  = 0.840). Conclusion  POEM is an effective and safe treatment for patients with achalasia. There is no difference in POEM outcomes for those patients with Chagasic or Idiopathic achalasia.